UJI DIAGNOSTIK METODE IMUNOSITOKIMIA NS1 VIRUS DENGUE, UNTUK DIAGNOSIS INFEKSI - Nafiandi Nafiandi; Ellyza Nasrul; Rismawati Yaswir (Indonesian Association of Clinical Pathologist and Medical laboratory, 2012)
NS1 protein is a nonstructural protein of dengue virus which are secreted into the blood. NS1 protein could be detected in blood upto nine days after the onset of illness that almost simultaneously with the occurrence of viremia. The purpose of this study is to knowthe result of diagnostic test method of immunocytochemical NS1 by RT-PCR on dengue virus infected patients which is diagnosed at Dr.M. Djamil hospital. Padang. The method of the research uses cross sectional analytically study with consecutive sampling of patientswho diagnosed as infected with dengue virus and treated in the interne ward of Dr. M. Djamil General Hospital Padang from Januaryup to August 2011. Patient ‘s venous blood was taken about 5 mL and then centrifuged 3500 rpm and then the serum is separated andstored at-20° C until the sample is examined. The examination of NS1 serum is carried out by immunocytochemical method followedby the inspection of RNA viruses and their serotypes by RT-PCR and continued by agarose gel electrophoresis on 1.5 up to 2%. From thesixty samples obtained showed: 71.6% tested positive immunocytochemical NS1, 28.4% negative immunocytochemical NS1, 76.7%positive RT-PCR and 23.3% negative RT-PCR, 23.9% Den-1, 43.3% Den-2, 26.1% Den-3, and 6.5% Den-4. The immunocytochemicalNS1 diagnostic test obtained RT-PCR sensitivity of 85%, specificity 71%, positive predictive value 90%, and negative predictive value59%. The immunocytochemical NS1 has a quite high sensitivity, and low specificity, where as the positive predictive value is quite high,but the negative predictive value is lower than the RT-PCR for the diagnosis of dengue virus infection.